2016
DOI: 10.1039/c6cp01946c
|View full text |Cite
|
Sign up to set email alerts
|

Conformational distortion of α-phenylethyl amine in cryogenic matrices – a matrix isolation VCD study

Abstract: The chiral amine α-phenylethyl amine (PEA) was isolated in cryogenic matrices and investigated using vibrational circular dichroism (VCD) and infrared spectroscopy. The potential energy surface (PES) of PEA features five different conformers connected by relatively low conformational transition states. Based on the IR spectra, it could be confirmed that all conformational energy barriers are passed at a deposition temperature of 20 K, and that only the global minimum conformation of PEA is populated in both ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 42 publications
1
25
0
4
Order By: Relevance
“…It has been shown that it is sometimes necessary to consider slight deviations from the local minima structures in order to accurately describe the VCD and also Raman optical activity (ROA) spectra of chiral molecules . Furthermore, we could recently show using matrix‐isolation VCD spectroscopy that the global minimum structure of the parent amine can even be easily distorted due to packing effects in the surrounding solid noble‐gas matrices . Along the same lines, we suspected that solute–solvent interactions might affect conformational preferences, in particular of the side groups, more than it could be captured by considering static local minima.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that it is sometimes necessary to consider slight deviations from the local minima structures in order to accurately describe the VCD and also Raman optical activity (ROA) spectra of chiral molecules . Furthermore, we could recently show using matrix‐isolation VCD spectroscopy that the global minimum structure of the parent amine can even be easily distorted due to packing effects in the surrounding solid noble‐gas matrices . Along the same lines, we suspected that solute–solvent interactions might affect conformational preferences, in particular of the side groups, more than it could be captured by considering static local minima.…”
Section: Resultsmentioning
confidence: 99%
“…[16] Computational details:G eometry optimizations and vibrational spectra calculations were carried out using the Gaussian09Rev.D .01 suite [18] of programsatthe B3PW91/6-31 ++G(2d,p) level of theory. 10 ha ccumulation time).…”
Section: Methodsmentioning
confidence: 99%
“…[12] MI-VCD spectroscopy was used to identify the conformational equilibrium of ac hiral alcohol and to follow its dimerization, [13] to assess the anharmonic contributions to the spectra of propylene oxide, [14] and to monitor the induction of optical activity into the vibrational motions of ammonia in its complex with methyl lactate. [16] In this contribution we show that MI-VCD spectroscopy is ap romising technique for gaining further spectroscopic insights into the photoisomerization stages of chiral molecular motors.T he ideal model system for this proof-of-principle study appeared to be as tructurally simple chiral switch featuring two photochemically interconvertible isomers, which can be selectively populated in high yields by irradiation with UV light of different wavelengths.Asuitable candidate was found in the camphorquinone imine 1 (Scheme 1), which was introduced by Lehn and co-workers in the context of their studies on the directionality of bond rotations in imine-based molecular motors. [16] In this contribution we show that MI-VCD spectroscopy is ap romising technique for gaining further spectroscopic insights into the photoisomerization stages of chiral molecular motors.T he ideal model system for this proof-of-principle study appeared to be as tructurally simple chiral switch featuring two photochemically interconvertible isomers, which can be selectively populated in high yields by irradiation with UV light of different wavelengths.Asuitable candidate was found in the camphorquinone imine 1 (Scheme 1), which was introduced by Lehn and co-workers in the context of their studies on the directionality of bond rotations in imine-based molecular motors.…”
mentioning
confidence: 95%
“…[16] Spektrenberechnungen: Struktur-und Energieoptimierungen und die Berechnung der Schwingungsspektren wurden mit Gaussian 09 Rev.D .01 [18] auf dem Theorieniveau B3PW91/6-31 ++G-(2d,p) durchgeführt. Die Grundlinienw urden korrigiert, indem Spektren des leeren Kaltkopfes subtrahiert wurden.…”
Section: Angewandte Chemieunclassified
“…[13] Weiterhin konnten neue theoretische Ansätze zur Beschreibung von anharmonischen Korrekturen am Beispiel von Methyloxiran getestet [14] sowie die Induktion optischer Aktivitäti nd ie Schwingungsmoden von Ammoniak nachgewiesen werden. [16] Wiehier gezeigt wird, ist die MI-VCD-Spektroskopie eine vielversprechende Methode,u ms pektroskopische Einblicke in die verschiedenen Schaltzustände molekularer Motoren zu Kk alten CsI-Kristall aufgesprüht wurde.N ach einem kurzen Aufwärmen der Matrix auf 30 Kw urde das in Abbildung 1g ezeigte MI-IR-Spektrum gemessen. [16] Wiehier gezeigt wird, ist die MI-VCD-Spektroskopie eine vielversprechende Methode,u ms pektroskopische Einblicke in die verschiedenen Schaltzustände molekularer Motoren zu Kk alten CsI-Kristall aufgesprüht wurde.N ach einem kurzen Aufwärmen der Matrix auf 30 Kw urde das in Abbildung 1g ezeigte MI-IR-Spektrum gemessen.…”
unclassified